2008
DOI: 10.1590/s1809-29502008000300010
|View full text |Cite
|
Sign up to set email alerts
|

Análise qualitativa dos efeitos da sonoforese com Arnica montana sobre o processo inflamatório agudo do músculo esquelético de ratos

Abstract: Este estudo visou verificar o efeito da sonoforese com Arnica montana sobre a fase inflamatória aguda de uma lesão muscular. Para isso, 40 ratos Wistar machos, lesados cirurgicamente, foram divididos em 4 grupos: controle (C), 10 ratos lesados e não tratados; grupo ultra-som (US), 10 lesados, tratados com US; grupo ultra-som com arnica (US+A), 10 ratos lesados, tratados com sonoforese de gel de arnica; grupo arnica (A), 10 ratos lesados, tratados com massagem de gel de arnica. O tratamento dos três grupos foi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
2
0
2
Order By: Relevance
“…47 Arnica also favors wound healing through the action of sesquiterpene lactones, its main active ingredients, which are responsible for the anti-inflammatory activity of this plant as demonstrated in various in vitro and in vivo studies. 25,48,49 Alfredo et al 50 showed that esters of helenalin and dihydrohelenalin are responsible for this effect. These components, analyzed by Seemann et al 51 and Staneva et al, 52 block the transcription factor NF-kB, inhibiting the migration and chemotaxis of neutrophils and, at higher concentrations, the synthesis of prostaglandins.…”
Section: Discussionmentioning
confidence: 99%
“…47 Arnica also favors wound healing through the action of sesquiterpene lactones, its main active ingredients, which are responsible for the anti-inflammatory activity of this plant as demonstrated in various in vitro and in vivo studies. 25,48,49 Alfredo et al 50 showed that esters of helenalin and dihydrohelenalin are responsible for this effect. These components, analyzed by Seemann et al 51 and Staneva et al, 52 block the transcription factor NF-kB, inhibiting the migration and chemotaxis of neutrophils and, at higher concentrations, the synthesis of prostaglandins.…”
Section: Discussionmentioning
confidence: 99%
“…O UST poderia atuar no processo de regeneração por meio de vibrações acústicas, as quais podem propiciar diversas alterações como aumento da síntese proteica e secreção de mastócitos, modificações na mobilidade dos fibroblastos, dentre outras 9 .…”
Section: Introductionunclassified
“…Arnica montana L. (Asteraceae) has been used in traditional Brazilian medicine in the form of tinctures, emulsions and creams for the treatment of pain and inflammation caused by bruising and edemas (BAL-ME, 1982;D'AMELIO, 1999). The anti-inflammatory properties of this plant are attributed to the presence of sesquiterpene lactones, principally esters of helenalin and dihydrohelenalin (ALFREDO et al, 2008), while the antioxidant activity is associated with the presence of quercetin, caffeic acid and chlorogenic acid (PYTEL ET AL., 2005;GANZERA ET AL., 2008). The pharmaceutical use of A. montana has been authorized by the Brazilian National Health Surveillance Agency (Agência Nacional de Vigilância Sanitária, ANVISA) at concentrations equivalent to 0.20 -0.25 mg/mg total sesquiterpene lactones for creams and ointments, and to 1 mg/mL total sesquiterpene lactones diluted 3 to 30 times for tinctures.…”
Section: Introductionmentioning
confidence: 99%